1986
DOI: 10.1055/s-0038-1661673
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Inhibits Platelet Aggregation by a Calcium-Independent Mechanism

Abstract: SummaryWe studied the inhibitory effects of the calcium channel blocker verapamil both on platelet aggregation and intracellular calcium [Ca2+]i in platelets loaded with a fluorescent indicator (quin 2).The inhibitory effects of verapamil on the platelet aggregation response to both thrombin and ionomycin were seen to be clearly dissociated from the verapamil-induced inhibition of the [Ca2+]i increase produced by these agonists. Verapamil-induced inhibition of platelet aggregation was also obtained when using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
3
0
3
Order By: Relevance
“…In this regard, it should be noted that verapamil treatment reduced the expression of cytokines and iNOS in the myocardium of T. cruzi-infected mice (Huang et al 1999b). In addition, verapamil has been demonstrated to alter vascular flow by inhibiting platelet aggregation (Bonadonna et al 1986) and by inhibiting the release of endothelin-1 by endothelial cells ( Haug et al 1998). Therefore, the actions of verapamil in ameliorating chagasic heart disease may be multi-factorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it should be noted that verapamil treatment reduced the expression of cytokines and iNOS in the myocardium of T. cruzi-infected mice (Huang et al 1999b). In addition, verapamil has been demonstrated to alter vascular flow by inhibiting platelet aggregation (Bonadonna et al 1986) and by inhibiting the release of endothelin-1 by endothelial cells ( Haug et al 1998). Therefore, the actions of verapamil in ameliorating chagasic heart disease may be multi-factorial.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of verapamil in the amelioration of chronic chagasic cardiomyopathy is not clear. However, verapamil has many actions, including the modulation of vascular flow, endothelin synthesis/release (Haug et al 1998), platelet aggregation (Bonadonna et al 1986) and inflammation (Berrebi et al 1994), which could explain the observations.…”
Section: Introductionmentioning
confidence: 99%
“…Marked basement membrane thickening in myocardial capillaries (up to 20 times the normal thickness) has been detected in chronic chagasic human hearts (84,85), similar to the thickening, either with or without multilayering, reported to occur in basement membranes of capillaries of patients with diabetes mellitus (86) and myxedema (87), in KK mice with genetically-transmitted cardiomyopathy associated with diabetes mellitus (88), and in renovascular hypertensive streptozotocin diabetic cardiomyopathic rats (89). Long-term administration of verapamil, a calcium channel blocker drug, markedly decreased myocardial inflammation and fibrosis in T. cruzi chronically-infected mice, producing a ten times decrease in mortality rate during a 70-day period of infection (90), probably through the maintenance of vascular perfusion due to its vasodilatatory action on smooth muscle cells and to its inhibitory effect on platelet aggregation (82,91). In vitro studies of infection demonstrated increased platelet adherence and aggregation related to infection-associated endothelial cell dysfunction (92).…”
Section: Role Of Microvascular Changesmentioning
confidence: 99%
“…Assim, o verapamil foi utilizado neste estudo por sua propriedade de vasodilatação da microcirculação (Tanowitz et al, 1989), bem como pelo seu efeito de diminuição da agregação plaquetária, este efeito independentemente da inibição da entrada de cálcio na célula (Bonadonna et al, 1986). Em estudo seminal de modelos experimentais com murinos infectados por T. cruzi, o uso de verapamil reduziu o dano miocárdico e a morbidade dos animais analisados (Morris et al, 1989).…”
Section: Distúrbios Perfusionais Miocárdicos Em Humanos Com a Ccdcunclassified